2006
DOI: 10.1111/j.1075-122x.2006.00297.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of HER-2 Status on Local Recurrence in Women with Stage I?II Breast Cancer Treated with Breast-Conserving Therapy

Abstract: This study was undertaken to determine whether overexpression of the oncogene HER-2 is associated with an increase in local recurrence in women with early stage breast cancer treated with breast-conserving therapy (BCT). A retrospective review of the medical records of all women treated with stage I-II invasive breast cancer from 1991 through 2001 was performed. Of 596 eligible patients treated in that time period, immunohistochemical testing for HER-2 expression was performed in 352 patients (59%): 266 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…That study did not include an assessment of margin status, a factor we found to be highly significant on multivariate analysis. Another study examined HER2 overexpression in tumors from 352 patients with stage I-II breast cancer treated with BCT and found no difference in the local recurrence rates between the HER2-positive and HER2-negative tumors (22). That study found very low recurrence rates in both the HER2-positive (0%) and the HER2-negative (2%) group.…”
Section: Discussionmentioning
confidence: 91%
“…That study did not include an assessment of margin status, a factor we found to be highly significant on multivariate analysis. Another study examined HER2 overexpression in tumors from 352 patients with stage I-II breast cancer treated with BCT and found no difference in the local recurrence rates between the HER2-positive and HER2-negative tumors (22). That study found very low recurrence rates in both the HER2-positive (0%) and the HER2-negative (2%) group.…”
Section: Discussionmentioning
confidence: 91%
“…The use of these three tumor markers to approximate biologic subtype has practical value in that these tumor markers are commonly available from retrospective data and guide the selection of targeted adjuvant systemic therapies (e.g., hormonal therapy, trastuzumab). Some studies have suggested an increased risk of local recurrence or local–regional recurrence after breast conservation treatment associated with the triple negative (basal-like) subtype or associated with tumors that are HER2 positive, although these associations have not been demonstrated uniformly in all studies [410, 23]. In the present study, no statistically significant differences in the 10-year rates of local recurrence or local– regional recurrence were observed based on biologic subtype (both P ≥ 0.76; Table 2; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Immunostaining was performed as previously described. 31,32 Briefly, cells were plated onto polyl-lysine Hydrobromide treated, flamed, glass coverslips in 4 cm dishes at 5 × 10 5 cells per dish and allowed to attach overnight. BPD-PDT was performed as described elsewhere in this paper, with dishes fixed at 5 and 60 min post illumination.…”
Section: Methodsmentioning
confidence: 99%